Analysis of areas, production and export potential for soft fruit and raspberries in Romania and Lithuania - Cristina Maria Sterie; Ispiryan Audrone (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
This research paper analyses the evolution of cultivated areas, production and export potential of soft fruits in Romania and Lithuania compared to the European Union, using Eurostat and Intracen data. The comparative analysis method revealed a significant increase in Romania, with cultivated areas and production increasing by more than 250% and 800% respectively. In contrast, Lithuania showed smaller fluctuations, with a steady increase of more than 9% in cultivated areas and about 41% in production. In the case of raspberry cultivation, Romania has seen a significant increase, while Lithuania has had a larger but recently decreasing cultivated area. Romania and Lithuania export to Germany, France, Serbia and Poland, Germany, the Netherlands respectively, with Germany identified as the main market for these fruits.
Keywords: Q10; Q12; Q14; Q19; 330; raspberries; export; Romania; Lithuania; berries